2016
DOI: 10.1088/0031-8949/91/9/095801
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic gap formation and condensation in the bilayer graphene structure

Abstract: We have studied the excitonic gap formation in the Bernal Stacked, bilayer graphene (BLG) structures at half-filling. Considering the local Coulomb interaction between the layers, we calculate the excitonic gap parameter and we discuss the role of the interlayer and intralayer Coulomb interactions and the interlayer hopping on the excitonic pair formation in the BLG. Particularly, we predict the origin of excitonic gap formation and condensation, in relation to the farthermost interband optical transition spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
84
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(95 citation statements)
references
References 87 publications
10
84
1
Order By: Relevance
“…In addition, it has been demonstrated that the excitonic insulator state and the excitonic condensation are two distinct phase transitions in the solid state [22,23], and the condensate states are due to the electronic phase stiffness [20,24], mechanism. Meanwhile, in the electronic bilayer systems, those mentioned phase transitions are indistinguishable as it was shown in references [12,21]. On the other hand, the inclusion of the dynamic screening and the full band structure favors the pairing and condensation [25][26][27].…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…In addition, it has been demonstrated that the excitonic insulator state and the excitonic condensation are two distinct phase transitions in the solid state [22,23], and the condensate states are due to the electronic phase stiffness [20,24], mechanism. Meanwhile, in the electronic bilayer systems, those mentioned phase transitions are indistinguishable as it was shown in references [12,21]. On the other hand, the inclusion of the dynamic screening and the full band structure favors the pairing and condensation [25][26][27].…”
Section: Introductionmentioning
confidence: 80%
“…A very large excitonic gap, found in a sufficiently broad interval of the repulsive interlayer Coulomb interaction parameter, given in reference [12], suggests that the level of intralayer density and chemical potential fluctuations in the BLG system, discussed in reference [11], are sufficiently small and do not affect the robust excitonic insulator state in the BLG. The excitonic condensation in the single BLG is principally possible in the case of the static interlayer screening regime [10].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations